Determinan Customer Satisfaction pada Pengguna Gopay di Kota Denpasar - Ni Luh Putu Chandra Kirana; Ni Wayan Wijayanti; Ni Luh Putu Sariani; Desak Made Sukarnasih (Jurnal Ilmiah Satyagraha, 2022)
This study aims to determine the effect of Experiential Marketing, E-Service Quality, Sales Promotion partially and simultaneously on Customer Satisfaction Gopay Users in Denpasar City. Data collection techniques used a questionnaire. The sample in this study were 75 respondents Gopay users in Denpasar City with the purposive sampling method. The data analysis technique using multiple linear regression. The results of this study indicate that Experiential Marketing, E-service Quality, Sales Promotion have a positive and significant effect partially and simultaneously on Customer Satisfaction Gopay users in Denpasar City. Suggestions that can be given by researchers to management are to improve experiential marketing so that customer satisfaction for Gopay users in Denpasar City is achieved.